2015
DOI: 10.1128/ec.00233-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of LFD-2, a Predicted Fringe Protein Required for Membrane Integrity during Cell Fusion in Neurospora crassa

Abstract: The molecular mechanisms of membrane merger during somatic cell fusion in eukaryotic species are poorly understood. In the filamentous fungus Neurospora crassa, somatic cell fusion occurs between genetically identical germinated asexual spores (germlings) and between hyphae to form the interconnected network characteristic of a filamentous fungal colony. In N. crassa, two proteins have been identified to function at the step of membrane fusion during somatic cell fusion: PRM1 and LFD-1. The absence of either o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…In addition to PRM1, earlier studies identified three additional factors, whose absence results in aberrant fusion and increased lysis rates during germling fusion, LFD-1, LFD-2, and FIG1 (Palma-Guerrero et al 2014, 2015. To test if the observed role of PEF1 is specific for DPrm1-caused defects or if it is of broader significance, we introduced the Dpef1 gene knockout into the Dlfd-1, Dlfd-2 and Dfig1 mutants and compared the lysis rates of the single and the respective double mutants on standard and Ca 2+ -reduced growth medium.…”
Section: The Lack Of Pef1 Results In Increased Lysis Rates In Lysis-pmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PRM1, earlier studies identified three additional factors, whose absence results in aberrant fusion and increased lysis rates during germling fusion, LFD-1, LFD-2, and FIG1 (Palma-Guerrero et al 2014, 2015. To test if the observed role of PEF1 is specific for DPrm1-caused defects or if it is of broader significance, we introduced the Dpef1 gene knockout into the Dlfd-1, Dlfd-2 and Dfig1 mutants and compared the lysis rates of the single and the respective double mutants on standard and Ca 2+ -reduced growth medium.…”
Section: The Lack Of Pef1 Results In Increased Lysis Rates In Lysis-pmentioning
confidence: 99%
“…They appear to ensure fusion fidelity, probably by organizing or spatially restricting the fusion machinery (Fleissner et al 2009;Palma-Guerrero et al 2014). The lack of LFD-2 or FIG1 also causes increased lysis rates, but no adhering membranes are observed, indicating distinct functions from PRM1 and LFD-1 (Palma-Guerrero et al 2015). Interestingly, the lysis rates in Dfig1 do not further increase in the absence of pef1.…”
Section: Pef1 Mediates Protection Against Membrane Fusion-induced Celmentioning
confidence: 98%
“…(A) Fluorescence microscopy of Δqc - 1 Δqc - 2 strain expressing either qc - 1 - sfGFP or qc - 2 - sfGFP . (B) Fluorescence microscopy of heterokaryotic cells expressing qc - 1 - sfGFP and sec61 - mCherry (53). Bars, 10 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Homokaryotic transformants were obtained as described above. The Sec61::mCherry strain was described previously (53). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation